Motivation, Leadership and Curriculum design: Engaging the Net Generation and 21st Century Learners - Koh, Caroline (Springer, 2016)
This book discusses the links between the basis of motivational, leadership and curricular constructs with regards to 21st century and net-generation learning. It brings together recent developments in motivation, educational leadership and curriculum design in order to offer a better understanding of what is already known and what is yet to be explored in these fields. It consists of a collection of findings on recent educational developments, including topics such as motivating the 21st century learner, leadership practices and influences, curriculum design and models, novel learning environments and 21st century learners and their needs.